Design of a Mathematical Unit in FPGA for the Implementation of the Control of a Magnetic Levitation System. (30th December 2008) - Raygoza-Panduro, Juan José; Ortega-Cisneros, Susana; Rivera, Jorge; de la Mora, Alberto
Abstract : This paper presents the design and implementation of an automatically generated mathematical unit, from a program developed in Java that describes the VHDL circuit, ready to be synthesized with the Xilinx ISE tool. The core contains diverse complex operations such as mathematical functions including sine and cosine, among others. The proposed unit is used to synthesize a sliding mode controller for a magnetic levitation system. This kind of systems is used in industrial applications requiring high level of mathematical calculations in small time periods. The core is designed to calculate trigonometric and arithmetic operations in such a way that each function is performed in a clock cycle. In this paper, the results of the mathematical core are shown in terms of implementation, utilization, and application to control a magnetic levitation system.